Metal organic framework adsorbent as well as preparation method and application thereof

By designing the metal-organic framework adsorbent Cu3(mtrz)2(ox)2, the problem of carbon dioxide separation in the prior art has been solved, and carbon dioxide separation with high selectivity and high adsorption capacity has been achieved. It is suitable for the efficient capture of carbon dioxide in flue gas and natural gas, and has the potential for green synthesis and large-scale application.

CN120900598APending Publication Date: 2025-11-07NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511017979.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing carbon capture technologies struggle to achieve high selectivity and high adsorption capacity for carbon dioxide separation with low energy consumption, especially in mixed systems of carbon dioxide and nitrogen or carbon dioxide and methane. Traditional adsorbents are energy-intensive during regeneration and difficult to apply on a large scale.

Method used

The metal-organic framework adsorbent Cu3(mtrz)2(ox)2 is used to construct a 3D framework with high-density open metal sites by coordinating 3-methyl-1H-1,2,4-triazole and oxalate ions with metal cations to form six- or four-coordination structures. Combined with ultra-micropores and a Lewis acidic environment, the specific adsorption of carbon dioxide is achieved.

Benefits of technology

It achieves efficient separation of carbon dioxide from nitrogen or methane, breaking through the technical bottleneck of traditional adsorption materials in balancing adsorption capacity and selectivity. It has high selectivity and adsorption capacity, and is suitable for efficient capture of carbon dioxide in flue gas and natural gas. Moreover, the synthesis method is green and pollution-free, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120900598A_ABST
    Figure CN120900598A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical separation, in particular to a metal organic framework adsorbent and a preparation method and application thereof. The chemical formula of the adsorbent is Cu3 (mtrz) 2 (ox) 2, a coordination structure of a hexa-coordinated octahedron and a tetracoordinated quadrangle is formed by Cu (II) and an organic ligand, and a 3D framework with high-density open metal sites is constructed. The adsorbent is synthesized by stirring at normal temperature by taking copper acetate, 3-methyl-1H-1, 2, 4-triazole and soluble oxalate as raw materials and water as a solvent, and large-scale synthesis and granulation can be realized. The adsorbent has high adsorption capacity and selectivity to CO2 / N2 and CO2 / CH4 systems by virtue of high-density open metal sites, ultramicro channels and a Lewis acid environment, can be used for adsorption separation of a fixed bed and the like, is low in regeneration energy consumption, and is suitable for separation of CO2 in flue gas.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of chemical separation technology, in particular to a metal-organic framework adsorbent and a preparation method and application thereof. BACKGROUND

[0002] In the field of petrochemical industry, efficient capture and separation of carbon dioxide is a key issue to balance ecological protection and economic benefits. Flue gas released by fossil fuel combustion is the main source of increasing carbon dioxide concentration in the atmosphere, among which coal, oil and natural gas contribute about 80% of global carbon emissions. With the continuous growth of industrial development and energy demand, this proportion will continue to rise. The main pollutants in flue gas usually include nitrogen (80%), carbon dioxide (12%-15%) and oxygen (5%-7%). Natural gas, as a clean energy, mainly contains methane, and also contains 30%-70% of carbon dioxide and trace amounts of nitrogen, methane and other gases. Separating carbon dioxide from natural gas and other gases in flue gas (such as carbon dioxide / nitrogen in flue gas and carbon dioxide / methane in natural gas system) is of great significance to reduce greenhouse effect and improve energy efficiency. However, the molecular kinetic diameters of carbon dioxide (3.3 Å), nitrogen (3.64 Å) and methane (3.8 Å) are very close, which makes it difficult to achieve high selective separation by conventional physical screening technology. Although amine-based solvent absorption method can selectively capture carbon dioxide through chemical action, its regeneration process consumes a large amount of heat energy, and its economy and sustainability are limited. Therefore, developing new adsorbent materials with high selectivity and low energy consumption has become the core direction to solve the problem of greenhouse gas treatment.

[0003] So far, two effective methods for treating carbon dioxide are carbon capture and storage (CCS) and direct air capture (DAC) technologies, both of which can effectively capture carbon dioxide. Exploring materials that can effectively capture carbon dioxide while reducing the greenhouse effect plays an important key role. A new generation of porous materials represented by metal-organic frameworks (MOFs) shows significant potential. MOFs can enhance the carbon dioxide adsorption capacity by flexibly regulating the pore size and surface chemical environment. For example, the introduction of uncoordinated metal sites or amino functional groups in the framework can enhance the polar interaction or acid-base binding effect of carbon dioxide, thereby improving the selective separation efficiency of carbon dioxide / nitrogen or carbon dioxide / methane mixed systems. Compared with traditional adsorbents such as activated carbon and zeolite, the designability of MOFs makes them perform better in low-concentration carbon dioxide capture scenarios such as environmental air or industrial exhaust gas. In addition, the physical adsorption technology based on MOFs can be combined with processes such as pressure swing adsorption (PSA) to replace the high-energy-consuming chemical adsorption method, significantly reducing the regeneration energy consumption and operating cost. This breakthrough not only provides an efficient solution for flue gas decarbonization and natural gas purification, but also lays a material foundation for achieving carbon neutralization and promoting green industrial transformation.

[0004] Existing carbon capture technologies can be used to capture carbon dioxide in industrial processes, including pre-combustion capture, oxy-combustion capture, and post-combustion capture, each with different advantages and limitations. For example, chemical adsorption usually has high selectivity, but in most cases, the combination of carbon dioxide chemical adsorbents and carbon dioxide is very firm, resulting in high energy loss for material regeneration. In contrast, physical adsorbents require less energy for regeneration, and the challenge is to find materials with good selectivity and adsorption capacity and are important in industrial application scenarios. SUMMARY

[0005] To solve the above problems, the present application provides a metal-organic framework adsorbent and its preparation method and application. The metal-organic framework adsorbent uses 3-methyl-1H-1,2,4-triazole and oxalate ions as organic ligands, and coordinates with metal cations to form a six-coordinated structure or a four-coordinated structure, obtaining a 3D metal-organic framework adsorbent with open metal sites. The adsorbent has a unique coordination structure and high density of open metal sites, combining the effect of ultra-micropore channel confinement and Lewis acid environment to achieve specific strong adsorption of CO2.

[0006] To achieve the above purpose, the technical scheme adopted by the present application is as follows: The purpose of this invention is to provide a metal-organic framework adsorbent with the chemical formula Cu3(mtrz)2(ox)2, wherein Cu is a metal cation, mtrz is 3-methyl-1H-1,2,4-triazole, and ox is soluble oxalate. The metal-organic framework material uses 3-methyl-1H-1,2,4-triazole and oxalate ions as organic ligands to coordinate with the metal cation, forming a six-coordinate structure or a four-coordinate structure, thereby obtaining a 3D metal-organic framework adsorbent with open metal sites.

[0007] When a six-coordinate structure is formed, Cu coordinates with the terminal N of two 3-methyl-1H-1,2,4-triazoles and the two O atoms on the same side of the oxalate molecules in two soluble oxalates, forming a hexahedral cluster secondary structural unit. When a four-coordinate structure is formed, two adjacent Cu atoms are respectively connected to the N atoms on the same side of two opposing 3-methyl-1H-1,2,4-triazoles, and then respectively coordinate with the two O atoms on the same side of the oxalate molecules in a single soluble oxalate, forming two four-coordinate structural units.

[0008] In a preferred embodiment of the present invention, the metal-organic framework adsorbent has a pore size of 0.3 nm to 2.0 nm and a pore volume of 0.2 cm³. 3 / g~0.8cm 3 / g, porosity 20%~50%, specific surface area 500m² 2 / g~1200m 2 / g.

[0009] Another object of the present invention is to provide a method for preparing the above-mentioned adsorbent, comprising the following steps: Metal-organic framework adsorbents were obtained by using a metal cation salt of acetate as a copper source, 3-methyl-1H-1,2,4-triazole and soluble oxalate as organic ligands, and water as a solvent, and by stirring at room temperature.

[0010] In a preferred embodiment of the present invention, the molar ratio of the acetate metal cation salt, 3-methyl-1H-1,2,4-triazole and soluble oxalate is 1:0.5~10:0.5~10.

[0011] A third objective of this invention is to provide an application of the above-mentioned adsorbent in the selective separation of carbon dioxide.

[0012] In a preferred embodiment of the present invention, when the adsorption temperature is -50℃ to 100℃ and the adsorption pressure is 0 bar to 10 bar, the mixed gas is contacted with the metal-organic framework adsorbent in the adsorption column to adsorb carbon dioxide from the mixed gas.

[0013] In a preferred embodiment of the present application, the mixed gas is one of carbon dioxide and nitrogen or carbon dioxide and methane; wherein the volume ratio of nitrogen to carbon dioxide is 1:99 to 99:1; and the volume ratio of methane to carbon dioxide is 1:99 to 99:1.

[0014] In a preferred embodiment of the present application, the contact mode of the mixed gas with the metal organic framework adsorbent is one of fixed bed adsorption, fluidized bed adsorption, and moving bed adsorption; and the contact adsorption process is at least one of single-tower or multi-tower pressure swing adsorption process, temperature swing adsorption process, and vacuum desorption adsorption process.

[0015] In a preferred embodiment of the present application, the contact mode of the mixed gas with the metal organic framework material is fixed bed adsorption, and the specific adsorption step is: when the adsorption temperature is 25℃ and the adsorption pressure is 1 bar, the mixed gas enters the fixed bed adsorption column filled with the metal organic framework material, the methane or nitrogen component preferentially penetrates the bed layer, and the carbon dioxide component is enriched in the bed layer. The flow rate of the mixed gas entering the fixed bed adsorption is one of 2 mL / min, 3 mL / min, and 5 mL / min.

[0016] Compared with the prior art, the present application has the beneficial effects that: 9. The present application provides a novel metal organic framework (MOF) adsorbent. 3-methyl-1H-1,2,4-triazole and oxalate ions are used as organic ligands to coordinate with metal cations to form six-coordinated structures or four-coordinated structures, thereby obtaining a 3D metal organic framework adsorbent with open metal sites. The adsorbent has the following characteristics: first, a unique dual-mode coordination structure, in which each Cu(II) metal ion forms two coordination configurations (hexa-coordinated octahedron + four-coordinated tetrahedron) with organic ligands, thereby constructing a regular 3D framework with high-density open metal sites (OMSs); second, a synergistic confinement effect, in which the supermicroporous channels and the extremely strong Lewis acidic environment synergistically act to realize specific recognition and strong adsorption of CO2 molecules.

[0017] 2. The metal organic framework material has high-density open metal sites and a synergistic confinement effect, not only exhibits excellent adsorption capacity for CO2, but also realizes the synergistic compatibility of adsorption capacity and selectivity, can efficiently capture CO2 from flue gas and natural gas, accurately recognizes CO2 molecules in flue gas, and breaks through the technical bottleneck that traditional adsorption materials are difficult to consider both adsorption capacity and separation selectivity, and exhibits ultra-high separation selectivity for CO2 / N2 and CO2 / CH4 systems.

[0018] 3、The application takes copper acetate, 3-methyl-1H-1,2,4-triazole (mtrz) and soluble oxalate (ox) as raw materials, and synthesizes the MOF adsorbent in an aqueous system through normal temperature stirring in one step. The normal temperature stirring reaction achieves the diffusion purpose, and heating and organic solvents are not needed, only appropriate water is needed, the synthesis method is green and pollution-free, simple and efficient. The precursor has high economy, when the molar ratio of metal salt, mtrz and ox is 3:2:2, large-scale production from gram level to kilogram level can be realized. The granules with mechanical strength can be made through the binder, and are suitable for industrial scale production and application, which provides a new discovery for the current MOF material product expensive and not easy to synthesize in large scale. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 The process route diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application.

[0020] Figure 2 The structure diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application.

[0021] Figure 3 The kilogram level synthesis sample diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application.

[0022] Figure 4 The granulation product diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application.

[0023] Figure 5 The X-ray diffraction diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application in different synthesis phase purity, different pH aqueous solution and different organic solution soaking stability test. Figure 5 The X-ray diffraction diagram of Cu3(mtrz)2(ox)2 in different synthesis phase purity is shown in a diagram, the X-ray diffraction diagram of Cu3(mtrz)2(ox)2 in different pH aqueous solution is shown in b diagram, and the X-ray diffraction diagram of Cu3(mtrz)2(ox)2 in different organic solution soaking is shown in c diagram.

[0024] Figure 6 The thermogravimetric curve diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application.

[0025] Figure 7 The 77K N2 adsorption isotherm diagram of the Cu3(mtrz)2(ox)2 adsorbent prepared in the embodiment 1 of the application. Figure 7 The N2 adsorption isotherm diagram at 77K is shown in a diagram, and the pore size distribution curve based on the Horvath-Kawazoe model analysis of the adsorption isotherm is shown in b diagram.

[0026] Figure 8 Adsorption isotherm plots of Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present invention for carbon dioxide, methane and nitrogen at 298 K.

[0027] Figure 9 Adsorption isotherm plots of Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present invention for carbon dioxide, methane and nitrogen at different temperatures. Figure 9 Fig. a is an adsorption isotherm plot of Cu3(mtrz)2(ox)2 adsorbent for carbon dioxide at different temperatures, Fig. b is an adsorption isotherm plot of Cu3(mtrz)2(ox)2 adsorbent for methane at different temperatures, and Fig. c is an adsorption isotherm plot of Cu3(mtrz)2(ox)2 adsorbent for nitrogen at different temperatures.

[0028] Figure 10 Kinetic adsorption plots of carbon dioxide, methane and nitrogen adsorption amount of Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present invention at 298 K as a function of time and pressure.

[0029] Figure 11 Carbon dioxide adsorption isotherm plots of small batch powder sample, kilogram scale synthesis sample and granulated product of Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present invention at 298 K.

[0030] Figure 12 Dynamic breakthrough plots of carbon dioxide / nitrogen and carbon dioxide / methane mixed gas components of Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present invention at 298 K. Figure 12 Fig. a is a dynamic breakthrough plot of carbon dioxide / nitrogen of Cu3(mtrz)2(ox)2 at 298 K, and Fig. b is a dynamic breakthrough plot of carbon dioxide / methane of Cu3(mtrz)2(ox)2 at 298 K.

[0031] Figure 13 Cyclic dynamic breakthrough plots of carbon dioxide / nitrogen and carbon dioxide / methane mixed gas components of Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present invention at 298 K. Figure 13 Fig. a is a cyclic dynamic breakthrough plot of carbon dioxide / nitrogen of Cu3(mtrz)2(ox)2 at 298 K, and Fig. b is a cyclic dynamic breakthrough plot of carbon dioxide / methane of Cu3(mtrz)2(ox)2 at 298 K. DETAILED DESCRIPTION

[0032] With reference to the accompanying drawings, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort should fall within the protection scope of the present application.

[0033] It should be noted that the professional terms used in the present application are only for the purpose of describing the specific embodiments, and are not intended to limit the protection scope of the present application. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present application can be purchased from the market or prepared by the existing method.

[0034] Various existing carbon capture technologies can be used to capture carbon dioxide in industrial processes, including pre-combustion capture, oxy-combustion capture and post-combustion capture, all of which have different advantages and limitations. For example, chemical adsorption usually has high selectivity, but in most cases, the combination of carbon dioxide chemical adsorbent and carbon dioxide is very firm, which brings high energy loss to material regeneration. In contrast, physical adsorbent requires less energy for regeneration, and the challenge is to find materials with good selectivity and adsorption capacity and simple and economical synthesis methods in industrial application scenarios. In addition, in optimizing the separation efficiency of carbon dioxide / nitrogen or carbon dioxide / methane, the adsorption capacity of carbon dioxide becomes a key parameter, which directly affects the efficiency of carbon dioxide / nitrogen and carbon dioxide / methane separation.

[0035] Therefore, first, the present application provides a metal organic framework adsorbent. The chemical formula of the metal organic framework adsorbent is Cu3(mtrz)2(ox)2, wherein Cu is a metal cation, mtrz is 3-methyl-1H-1,2,4-triazole, and ox is a soluble oxalate salt; the metal organic framework material uses 3-methyl-1H-1,2,4-triazole and oxalate ion as organic ligand, and coordinates with the metal cation to form a six-coordinated structure or a four-coordinated structure, thereby obtaining a 3D metal organic framework adsorbent with open metal sites.

[0036] When forming a six-coordinated structure, Cu is coordinated with two top N of 3-methyl-1H-1,2,4-triazole and two O on the same side of oxalate molecules in the soluble oxalate salt, forming a hexahedral cluster secondary structure unit; when forming a four-coordinated structure, two adjacent Cus are respectively connected with two N on the same side of 3-methyl-1H-1,2,4-triazole, and then respectively coordinated with two O on the same side of oxalate molecules in the separate soluble oxalate salt, forming two four-coordinated structure units.

[0037] It should be noted that the metal organic framework adsorbent provided in the present application, in addition to having the above-mentioned regular 3D framework with high-density open metal sites (OMSs), also has a synergistic confinement effect, a synergistic effect of ultra-micropores and a very strong Lewis acid environment, to realize specific recognition and strong adsorption of CO2 molecules.

[0038] The pore size of the metal organic framework adsorbent is 0.3nm~2.0nm, the pore volume is 0.2cm 3 / g~0.8cm 3 / g, the porosity is 20%~50%, and the specific surface area is 500m 2 / g~1200m 2 / g.

[0039] Secondly, the present application provides a preparation method of the above-mentioned metal organic framework adsorbent. Acetate metal cation salt is used as the copper source, 3-methyl-1H-1,2,4-triazole and soluble oxalate are used as organic ligands, and water is used as the solvent, and the stirring reaction is carried out at room temperature to obtain the metal organic framework adsorbent.

[0040] It should be noted that the acetate metal cation salt is selected as the copper source because, in the previous research, after trying and screening a plurality of copper sources, it is found that the copper source has the optimal reaction activity and coordination performance. Specifically, the reasons are as follows: first, the copper ion has an empty 3d orbital, which can effectively accept the electron pair provided by the ligand, and then form a coordination bond. Second, there are three coordination N atoms in the organic ligand 3-methyl-1H-1,2,4-triazole, and third, the oxalate has four O atoms that can participate in coordination. The combination of such polydentate ligands and central copper ions can form a variety of coordination environments and have the potential to form metal organic frameworks.

[0041] The molar ratio of the acetate metal cation salt, 3-methyl-1H-1,2,4-triazole and soluble oxalate is 1:0.5~10:0.5~10. In the present application, the soluble oxalate can be decomposed and ionized into oxalate ions in water, and the oxalate includes but is not limited to sodium oxalate or potassium oxalate. In a preferred embodiment, the oxalate is sodium oxalate or potassium oxalate. In the present application, copper is selected as the basis to explore the molar ratio of 3-methyl-1H-1,2,4-triazole and oxalate from 0.5 or more, mainly based on the coordination characteristics of copper ions and the binding ability of ligands. Copper generally has 4 / 6 coordination bonds, 3-methyl-1H-1,2,4-triazole has three coordination bonds, and the four oxygen atoms of oxalate can be coordinated.

[0042] The application adopts normal temperature stirring method, stirring for 24 hours, aiming to accelerate the mixing of reactants, promote the diffusion of substances in the system, without heating and the addition of organic solvents, only with appropriate amount of water, the synthesis method is green and pollution-free, the precursor is economical and can be synthesized on a large scale, and can be granulated to form particles with certain mechanical hardness.

[0043] Finally, the application provides an application of the above-mentioned metal organic framework adsorbent in selectively separating carbon dioxide.

[0044] The process of the above-mentioned application is that, at an adsorption temperature of-50℃ to 100℃ and an adsorption pressure of 0bar to 10bar, the mixed gas and the metal organic framework adsorbent in the adsorption column are contacted to adsorb carbon dioxide in the mixed gas. Generally, the higher the adsorption temperature, the lower the adsorption capacity of the gas; the higher the adsorption pressure, the higher the adsorption capacity of the gas.

[0045] The mixed gas is one of carbon dioxide and nitrogen or carbon dioxide and methane; wherein the volume ratio of nitrogen to carbon dioxide is 1:99 to 99:1; the volume ratio of methane to carbon dioxide is 1:99 to 99:1. The adsorption capacity of the material for carbon dioxide, nitrogen and methane is different, so it is necessary to use a mixed gas for evaluation, and the metal organic framework material has different phenomena for different proportions of two gas mixtures.

[0046] The contact mode of the mixed gas and the metal organic framework adsorbent is one of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption; the contact adsorption process is at least one of single-tower or multi-tower pressure swing adsorption process, temperature swing adsorption process and vacuum desorption adsorption process.

[0047] The contact mode of the mixed gas and the metal organic framework material is fixed bed adsorption, and the specific adsorption steps are as follows: at an adsorption temperature of 25℃ and an adsorption pressure of 1bar, the mixed gas enters the fixed bed adsorption column filled with the metal organic framework material, the methane or nitrogen component preferentially penetrates the bed layer, and the carbon dioxide component is enriched in the bed layer. The flow rate of the mixed gas entering the fixed bed adsorption is one of 2mL / min, 3mL / min and 5mL / min.

[0048] The metal organic framework material has high density of open metal sites and synergistic confinement effect, not only exhibits excellent adsorption capacity for CO2, but also realizes the synergistic compatibility of adsorption capacity and selectivity, can efficiently capture CO2 from flue gas and natural gas, accurately identifies CO2 molecules in flue gas, and breaks through the technical bottleneck that traditional adsorption materials are difficult to balance adsorption capacity and separation selectivity, and presents ultra-high separation selectivity for CO2 / N2 and CO2 / CH4 systems.

[0049] The following is further illustrated by specific examples.

[0050] Example 1 A method for preparing a metal-organic framework adsorbent, the synthetic route of which is shown in Figure 1 comprising the following steps: 0.050 g of 3-methyl-lH-l,2,4-triazole corresponding to 0.6 mmol and 0.081 g of sodium oxalate corresponding to 0.6 mmol were mixed and then added to a 50 mL round bottom flask containing 15 mL of an aqueous solution, stirring at a speed of 600 r / min. 0.180 g of copper acetate monohydrate corresponding to 0.9 mmol was dissolved in 10 mL of water and then slowly injected into the round bottom flask. Stirring was carried out at room temperature for 24 h, and the solution was filtered to obtain a blue powder sample, which was a metal-organic framework adsorbent, named Cu3(mtrz)2(ox)2 adsorbent, the structure of which is shown in Figure 2 .

[0051] Example 2 A method for preparing a metal-organic framework adsorbent, the synthetic route of which is shown in Figure 1 comprising the following steps: 0.050 g of 3-methyl-lH-l,2,4-triazole corresponding to 0.6 mmol and 0.081 g of sodium oxalate corresponding to 0.6 mmol were mixed and then added to a 50 mL round bottom flask containing 15 mL of an aqueous solution, stirring at a speed of 600 r / min. 0.180 g of copper acetate monohydrate corresponding to 0.9 mmol was dissolved in 10 mL of water and then slowly injected into the round bottom flask. Stirring was carried out at room temperature for 24 h, and the solution was filtered to obtain a blue powder sample, which was a metal-organic framework adsorbent, named Cu3(mtrz)2(ox)2 adsorbent, the structure of which is shown in

[0052] Example 3 A method for preparing a metal-organic framework adsorbent, the synthetic route of which is shown in Figure 1 comprising the following steps: 0.050 g of 3-methyl-lH-l,2,4-triazole corresponding to 0.6 mmol and 0.081 g of sodium oxalate corresponding to 0.6 mmol were mixed and then added to a 50 mL round bottom flask containing 15 mL of an aqueous solution, stirring at a speed of 600 r / min. 0.180 g of copper acetate monohydrate corresponding to 0.9 mmol was dissolved in 10 mL of water and then slowly injected into the round bottom flask. Stirring was carried out at room temperature for 24 h, and the solution was filtered to obtain a blue powder sample, which was a metal-organic framework adsorbent, named Cu3(mtrz)2(ox)2 adsorbent, the structure of which is shown in

[0053] Since the metal-organic framework adsorbents prepared in Examples 1 to 3 have similar structures and performance, the metal-organic framework adsorbent prepared in Example 1 was used as a representative in subsequent tests and experiments.

[0054] A scale-up experiment was conducted on the metal-organic framework adsorbent prepared in Example 1. The scale-up experiment was conducted using the same method as the powder synthesis, except that the amount of reactants was increased by 1000 times. The raw materials were stirred at 800 rpm in a 20 L reactor. Then, an aqueous solution of copper acetate was slowly injected into the reactor from the top. After stirring at room temperature for 24 h, the filtered solution produced a blue powder. This powder was washed three times with deionized water and dried at room temperature for 12 h to obtain 110.2 g of Cu3(mtrz)2(ox)2 sample, with a yield still reaching 73.8%. The product obtained in the scale-up experiment is shown below. Figure 3 As shown.

[0055] Granulation experiments were conducted on the metal-organic framework adsorbent prepared in Example 1. The granulation experiment included the following steps: 50 mg of 5% sodium carboxymethyl cellulose (CMC) was used as a binder, and 10 g of Cu3(mtrz)2(ox)2 powder was ground in a quartz mill. The powder was then placed on a wooden board, and a small amount of water was sprayed onto the sample. The moistened powder was rolled into spheres by hand, and the sample was then dried in a vacuum oven at 60°C for 12 hours to remove water molecules from the spheres. The granulated product is shown below. Figure 4 As shown.

[0056] Figure 5 The X-ray diffraction patterns are shown for the stability tests of the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of this invention under different phase purities, different pH aqueous solutions, and different organic solutions. Figure 5 Figure a shows the X-ray diffraction patterns of Cu3(mtrz)2(ox)2 at different phase purities; Figure b shows the X-ray diffraction patterns of Cu3(mtrz)2(ox)2 in aqueous solutions with different pH values; and Figure c shows the X-ray diffraction patterns of Cu3(mtrz)2(ox)2 after immersion in different organic solutions. Figure 5 It can be seen that the XRD patterns of activation, synthesis, and simulation confirmed that the configuration of Cu3(mtrz)2(ox)2 powder after synthesis and activation is consistent with the single crystal analytical structure. Experiments by soaking the material in various solvents and aqueous solutions with different pH values ​​for 3 days showed that Cu3(mtrz)2(ox)2 material only underwent significant changes at pH=1 or pH=13, but the characteristic peaks shown in the PXRD patterns of other solutions did not change significantly, indicating that the synthesized Cu3(mtrz)2(ox)2 material has good solvent stability and pH stability.

[0057] Figure 6This is a thermogravimetric curve of the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of the present invention. Figure 6 It can be seen that under N2 atmosphere, the weight loss rate of Cu3(mtrz)2(ox)2 is 23.1% during the heating from 30℃ to 134.5℃, which is the result of the loss of water molecules in the framework and water molecules bound to OMSs. Cu3(mtrz)2(ox)2 collapses at temperatures above 169.2℃, indicating that Cu3(mtrz)2(ox)2 material has low stability in high-temperature environments.

[0058] Figure 7 This is the 77K N2 adsorption isotherm of the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of this invention. Figure 7 Figure a shows the N2 adsorption isotherm at 77 K, and figure b shows the pore size distribution curve of the adsorption isotherm based on the Horvath-Kawazoe model. Figure 7 The permanent porosity of Cu3(mtrz)2(ox)2 was determined by the N2 adsorption isotherm at 77 K, and the surface area of ​​Brunauer-Emmett-Teller (BET) was found to be 913.0 m². 2 / g, the calculated pore volume is 0.43cm³. 3 / g, with a pore size distribution of approximately 5.5 Å.

[0059] Figure 8 This is an adsorption isotherm diagram of carbon dioxide, methane, and nitrogen gas at 298 K for the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of this invention. Figure 8 It can be seen that the adsorption capacities of Cu3(mtrz)2(ox)2 for carbon dioxide, methane and nitrogen are 5.66 mmol / g, 1.37 mmol / g and 0.34 mmol / g, respectively, which demonstrates the separation potential of these two materials for flue gas mixtures.

[0060] Figure 9 The images show adsorption isotherms of the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of this invention for carbon dioxide, methane, and nitrogen at different temperatures. Figure 9 Figure a shows the adsorption isotherms of carbon dioxide by Cu3(mtrz)2(ox)2 adsorbent at different temperatures; Figure b shows the adsorption isotherms of methane by Cu3(mtrz)2(ox)2 adsorbent at different temperatures; and Figure c shows the adsorption isotherms of nitrogen by Cu3(mtrz)2(ox)2 adsorbent at different temperatures. Figure 9 It can be seen that Cu3(mtrz)2(ox)2 material can maintain good adsorption performance at different temperatures.

[0061] Figure 10 The kinetic adsorption curves of carbon dioxide, methane and nitrogen adsorbed by the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of the present application at 298 K were plotted against time and pressure. The results are shown in Figure 2. Figure 10 It can be seen that carbon dioxide, methane and nitrogen all reached adsorption saturation at about 9 min; and the dynamic adsorption amounts of carbon dioxide, methane and nitrogen were close to their static adsorption amounts when the adsorption reached saturation.

[0062] Figure 11 The carbon dioxide adsorption isotherm plots of the small batch powder sample, kilogram synthesis sample and granulated product of the Cu3(mtrz)2(ox)2 adsorbent prepared in Example 1 of the present application at 298 K were plotted. The results are shown in Figure 3. Figure 11 It can be seen that the product of large-scale synthesis exhibited good carbon dioxide adsorption performance, and its performance was not significantly deteriorated compared with the small batch synthesis, and its carbon dioxide adsorption amount was still as high as 5.12 mmol / g. In addition, the spherical solid of Cu3(mtrz)2(ox) (large-scale synthesis product) was prepared by the granulation method using sodium carboxymethyl cellulose (mass fraction of 5%) as a binder, and its performance was not significantly deteriorated, which verified the great potential of Cu3(mtrz)2(ox) in practical applications.

[0063] Application Example 1 The Cu3(mtrz)2(ox)2 material prepared in Example 1 was loaded into a fixed bed adsorption column with an inner diameter of 6 mm and a length of 20 cm, and at 298 K and 1 bar, the mixed gas of carbon dioxide and nitrogen with a volume ratio of 15:85 and the mixed gas of carbon dioxide / methane with a volume ratio of 10:90 were flowed through the adsorption column at a fixed flow rate of 2.0 mL / min, and the adsorption was stopped when the adsorption column was completely penetrated. The adsorption column was regenerated by helium sweeping at room temperature, or was regenerated by desorption with a vacuum pump at room temperature, and the vacuum degree was 0.05 bar.

[0064] Application Example 2 The Cu3(mtrz)2(ox)2 material prepared in Example 1 was loaded into a fixed bed adsorption column with an inner diameter of 6 mm and a length of 20 cm, and at 298 K and 1 bar, the mixed gas of carbon dioxide and nitrogen with a volume ratio of 15:85 and the mixed gas of carbon dioxide / methane with a volume ratio of 10:90 were flowed through the adsorption column at a fixed flow rate of 3.0 mL / min, and the adsorption was stopped when the adsorption column was completely penetrated. The adsorption column was regenerated by helium sweeping at room temperature, or was regenerated by desorption with a vacuum pump at room temperature, and the vacuum degree was 0.05 bar.

[0065] Application Example 3 The Cu3(mtrz)2(ox)2material prepared in Example 1 was packed into a fixed bed adsorption column with an inner diameter of 6 mm and a length of 20 cm. At 298 K and 1 bar, the dynamic breakthrough curves of the mixture of carbon dioxide and nitrogen (volume ratio of 15:85) and the mixture of carbon dioxide and methane (volume ratio of 10:90) were measured at a fixed flow rate of 5.0 mL / min. The adsorption was stopped when the column was completely penetrated. The column was regenerated by helium sweeping at room temperature or by vacuum pumping at room temperature, and the vacuum degree was 0.05 bar.

[0066] Figure 12 The dynamic breakthrough curves of the Cu3(mtrz)2(ox)2adsorbent prepared in Example 1 of the present application at 298 K were measured for the mixture of carbon dioxide and nitrogen (volume ratio of 15:85, flow rate of 2.0 mL / min, 3.0 mL / min, and 5.0 mL / min) and the mixture of carbon dioxide and methane (volume ratio of 10:90, flow rate of 2.0 mL / min, 3.0 mL / min, and 5.0 mL / min). In the figures, Figure 12 In FIG. a, the dynamic breakthrough curves of Cu3(mtrz)2(ox)2at 298 K for the mixture of carbon dioxide and nitrogen (volume ratio of 15:85, flow rate of 2.0 mL / min, 3.0 mL / min, and 5.0 mL / min) are shown. In FIG. b, the dynamic breakthrough curves of Cu3(mtrz)2(ox)2at 298 K for the mixture of carbon dioxide and methane (volume ratio of 10:90, flow rate of 2.0 mL / min, 3.0 mL / min, and 5.0 mL / min) are shown. It can be seen from the figures that Figure 12 It can be seen that Cu3(mtrz)2(ox)2achieves efficient CO2 / N2separation at different flow rates. At a flow rate of 2.0 mL / min, N2is first penetrated out of the column, and CO2gas is not penetrated out until 92 min. Moreover, at flow rates of 3 mL / min and 5 mL / min, CO2can be maintained in the column for 55 min and 37 min, respectively, which shows the great potential of Cu3(mtrz)2(ox)2in CO2 / N2separation. Similarly, at flow rates of 2 mL / min, 3 mL / min, and 5 mL / min, the breakthrough interval time between CO2and CH4is about 69 min, 58 min, and 19 min, respectively, which also shows the potential of Cu3(mtrz)2(ox)2in CO2 / CH4separation, and indicates that this material can provide certain reference significance for the actual separation of flue gas and natural gas.

[0067] Figure 13The cyclic dynamic breakthrough curves of the Cu3(mtrz)2(ox)2 adsorbent prepared for Example 1 of the present application at 298 K for carbon dioxide / nitrogen and carbon dioxide / methane mixed gas components (volume ratio 15:85 and 10:90, flow rate 2.0 mL / min) are shown in FIG. 1. In FIG. 1, Figure 13 FIG. 1 is a graph showing the cyclic dynamic breakthrough curves of Cu3(mtrz)2(ox)2 at 298 K for carbon dioxide / nitrogen (volume ratio 15:85, flow rate 2.0 mL / min) in a, and carbon dioxide / methane (volume ratio 10:90, flow rate 2.0 mL / min) in b. As shown in FIG. 1, Figure 13 It can be seen that no deterioration in breakthrough time was observed in the multiple consecutive cycles, i.e., the Cu3(mtrz)2(ox)2 maintained a relatively excellent cycle capacity.

[0068] It should be noted that when numerical ranges are used herein, it is intended to include every number within the range and any number that falls within the range. As a result, unless the context clearly indicates otherwise, it is intended that, within the scope of the appended claims, equivalents to the examples can be used as a substitution for the examples. While the preferred embodiments of the application have been described above, it will be obvious that many modifications and variations of the present application are possible in light of the above teachings. It is intended that the appended claims cover all such modifications and variations of the application. Thus, it should be apparent that certain aspects of the application can be embodied in a variety of other forms; therefore, the specific embodiments detailed herein are to be construed illustrative only and not limitative of the scope of the application.

[0069] Obviously, numerous modifications and variations of the present application are possible in light of the above teachings. It is therefore to be understood that within the scope of the appended claims, the application can be practiced otherwise than as specifically described herein.

Claims

1. A metal organic framework adsorbent characterized in that, The chemical formula of the metal organic framework adsorbent is Cu3(mtrz)2(ox)2, wherein Cu is a metal cation, mtrz is 3-methyl-1H-1,2,4-triazole, and ox is a soluble oxalate; the metal organic framework material is coordinated with 3-methyl-1H-1,2,4-triazole and oxalate ions and metal cations to form a six-coordinated structure or a four-coordinated structure, thereby obtaining a 3D metal organic framework adsorbent with open metal sites; When the six-coordinated structure is formed, the Cu is coordinated with two top N of the 3-methyl-1H-1,2,4-triazole and two O of the oxalate molecules on the same side of the two soluble oxalates, thereby forming a hexahedral cluster secondary structure unit; When the four-coordinated structure is formed, two adjacent Cus are connected with two opposite N of the 3-methyl-1H-1,2,4-triazole on the same side, and then are coordinated with two O on the same side of the oxalate molecules in the separate soluble oxalates, thereby forming two four-coordinated structure units.

2. The metal-organic framework adsorbent of claim 1, wherein, The metal organic framework adsorbent has a pore size of 0.3nm~2.0nm, a pore volume of 0.2cm 3 / g~0.8cm 3 / g, a porosity of 20%~50%, a specific surface area of 500m 2 / g~1200m 2 / g.

3. A method of preparing the metal organic framework adsorbent of claim 1 or claim 2, characterized in that, The method comprises the following steps: The metal organic framework adsorbent is obtained by stirring at room temperature using an acetate metal cation salt as a copper source, 3-methyl-1H-1,2,4-triazole and a soluble oxalate as organic ligands, and water as a solvent.

4. The method of claim 3, wherein the metal organic framework adsorbent is prepared by a method comprising: The molar ratio of the acetate metal cation salt, 3-methyl-1H-1,2,4-triazole and the soluble oxalate is 1:0.5-10:0.5-10.

5. Use of the metal organic framework adsorbent according to claim 1 or claim 2 for selectively separating carbon dioxide.

6. Use of the metal organic framework adsorbent of claim 5 for the selective separation of carbon dioxide, characterized in that, The metal organic framework adsorbent in the adsorption column is contacted with a mixed gas at an adsorption temperature of-50-100 DEG C and an adsorption pressure of 0-10 bar to adsorb carbon dioxide in the mixed gas.

7. Use of a metal organic framework adsorbent according to claim 6 for the selective separation of carbon dioxide, characterized in that, The mixed gas is one of carbon dioxide and nitrogen or carbon dioxide and methane; wherein the volume ratio of nitrogen to carbon dioxide is 1:99-99:1; and the volume ratio of methane to carbon dioxide is 1:99-99:

1.

8. Use of the metal organic framework adsorbent of claim 6 for the selective separation of carbon dioxide, characterized in that, The contact mode of the mixed gas and the metal organic framework adsorbent is one of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption; and the contact adsorption process is at least one of single-tower or multi-tower pressure swing adsorption process, temperature swing adsorption process and vacuum desorption adsorption process.

9. Use of the metal organic framework adsorbent of claim 6 for the selective separation of carbon dioxide, characterized in that, The contact mode of the mixed gas and the metal organic framework material is fixed bed adsorption, and the specific adsorption steps are as follows: the mixed gas enters a fixed bed adsorption column filled with the metal organic framework material at an adsorption temperature of 25 DEG C and an adsorption pressure of 1 bar, and the methane or nitrogen component preferentially penetrates the bed layer, and the carbon dioxide component is enriched in the bed layer. The flow rate of the mixed gas entering the fixed bed adsorption column is one of 2 mL / min, 3 mL / min and 5 mL / min.